Further education in England: at the crossroads between a national, competitive sector and a locally collaborative system?. Issue 3 (3rd April 2019) - Hodgson, Ann; Spours, Ken
ABSTRACT: During the 25 years since Incorporation, when further education (FE) colleges were taken out of local government control, FE in England has been shaped by processes of marketisation to become a competitive national sector that has increasingly diverged from the more 'collaborative system logic' of the other three countries of the UK. However, following recent government reforms, FE in England appears to have reached a crossroads with the opportunity to participate in a more collaborative skills-based landscape at the local and sub-regional levels. This article brings together evidence from historical and international comparative system analysis, a series of UK-wide seminars and in-depth research on the Area-Based Review of FE colleges to assess the strategic direction of FE in England at this critical juncture. We argue that English FE providers can take advantage of these trends to make a transition from a reactive, competitive national sector towards a more collaborative, regional and sub-regional system focused on inclusive economic and skills development. The article concludes that the potential for cross-UK policy learning depends on whether FE in England gradually transitions towards a more collaborative future that could bring it closer to FE and skills systems in Scotland, Wales and Northern Ireland.